LIVING WITH ARTHRITIS - Gupta, Anita (SCHOOL SCIENCE, 2013)
Arthritis, known as common cause of disability affects almost one person in every family and actually refers to a group of over 100 different conditions. Osteoarthritis and Rheumatoid Arthritis (RA) are two commonest types of the diseases. These are not only found in humans but also throughout the animal kingdom. Some skeletons of prehistoric animals displayed in museums show signs of an arthriric condition. It is estimated that about one per cent of the global population suffers from one or the other types of arthritis affecting some of the 264 synovial joints present in the human system. Arthritis is the name given to a disease involving principally the joints and is characterised by pain, stiffness, swelling and finally loss of function. In this disease the lining of the joints gets inflammed and can result in damage to its surface. The exact reason why the disease occurs is not known. Patients of arthritis may become so incapacitated that they are unable to perform even the most routine tasks. This incapacity combined with pain and deformity caused by disease and with inforced idleness and dependency often results in a sense of hopelessness and depression.